THE EFFECT OF WORK FACILITIES AND LEADERSHIP STYLE TEACHER PERFORMANCE AT STATE 2 SMA SCHOOL BINJAI CITY - Slamet Widodo; Lambok Manurung (SEAN Institute, 2022)
SMA Negeri 2 Kota Binjai is one of the most favorite high schools in Binjai City and one of the oldest high school no. 2 in Binjai City so that researchers feel challenged to provide input and solutions to advance SMA Negeri 2 Binjai City. This study aims to examine the effect of work facilities and leadership style on teacher performance, which has a total sample of 70 respondents. This study uses multiple linear regression analysis with data processing using SPSS 22.0. The results of this study can be seen if work facilities and leadership style have a partial or simultaneous effect on teacher performance with a large coefficient of determination of 0.785 or 78.5% and it can be said that the close relationship between the independent variables and the dependent variable is strong. While the rest is in other factors.